Study on the predictive value of early microcirculation perfusion indicators combined with neuroelectrophysiological monitoring for the occurrence and prognosis of sepsis-associated encephalopathy in neurocritical care patients - Wang, Zhenyu; Cui, Yonghe (Frontiers in Neurology, 2025)
BackgroundSepsis-associated encephalopathy (SAE) is a common neurological complication in neurocritical care units, characterized by diffuse brain dysfunction without direct central nervous system infection. Early identification and prognosis assessment remain challenging due to the lack of specific diagnostic criteria.ObjectiveTo evaluate the predictive value of early microcirculation perfusion indicators combined with neuroelectrophysiological monitoring for the occurrence and prognosis of SAE in neurocritical care patients.MethodsThis prospective observational study enrolled 200 neurocritical care patients with sepsis over a 2-year period. Sublingual microcirculation was assessed using sidestream dark field (SDF) videomicroscopy, measuring perfused vessel density (PVD), microvascular flow index (MFI), and perfused boundary region (PBR). Continuous electroencephalography (cEEG) monitoring was performed for 72 h. Serum biomarkers including neuron-specific enolase (NSE) and S100 calcium-binding protein B (S100B) were measured at admission and serially. The primary outcome was the development of SAE, and secondary outcomes included 28-day mortality and neurological function at 90 days.ResultsAmong 200 patients, 134 (67%) developed SAE. Patients with SAE showed significantly reduced PVD (8.2 ± 2.1 vs. 12.4 ± 2.8 mm/mm2, p < 0.001) and MFI (1.8 ± 0.6 vs. 2.6 ± 0.4, p < 0.001) compared to non-SAE patients. The combination of microcirculation parameters with EEG abnormalities yielded an area under the curve (AUC) of 0.92 (95% CI: 0.88–0.96) for predicting SAE. Early microcirculation-EEG patterns were strongly associated with 28-day mortality (HR: 3.45, 95% CI: 2.12–5.61, p < 0.001) and poor neurological outcomes at 90 days.ConclusionThe combination of early microcirculation perfusion indicators with neuroelectrophysiological monitoring provides excellent predictive value for SAE occurrence and prognosis in neurocritical care patients. This multimodal approach may facilitate early identification and risk stratification.